Siplizumab selectively depletes effector memory T cells and promotes a relative expansion of alloreactive regulatory T cells in vitro. Issue 1 (13th August 2019) - Podestà, Manuel A.; Binder, Christian; Sellberg, Felix; DeWolf, Susan; Shonts, Brittany; Ho, Siu‐Hong; Obradovic, Aleksandar; Waffarn, Elizabeth; Danzl, Nichole; Berglund, David; Sykes, Megan
Abstract : Siplizumab, a humanized anti‐CD2 monoclonal antibody, has been used in conditioning regimens for hematopoietic cell transplantation and tolerance induction with combined kidney‐bone marrow transplantation. Siplizumab‐based tolerance induction regimens deplete T cells globally while enriching regulatory T cells (Tregs) early posttransplantation. Siplizumab inhibits allogeneic mixed‐lymphocyte reactions (MLRs) in vitro. We compared the impact of siplizumab on Tregs versus other T cell subsets in HLA‐mismatched allogeneic MLRs using PBMCs. Siplizumab predominantly reduced the percentage of CD4 + and CD8 + effector memory T cells, which express higher CD2 levels than naïve T cells or resting Tregs. Conversely, siplizumab enriched proliferating CD45RA − FoxP3 HI cells in MLRs. FoxP3 expression was stable over time in siplizumab‐containing cultures, consistent with enrichment for bona fide Tregs. Consistently, high‐throughput TCRβ CDR3 sequencing of sorted unstimulated and proliferating T cells in MLRs revealed selective expansion of donor‐reactive Tregs along with depletion of donor‐reactive CD4 + effector/memory T cells in siplizumab‐containing MLRs. These results indicate that siplizumab may have immunomodulatory functions that may contribute to its success in tolerance‐inducing regimens. Our studies also confirm that naïve in addition to effector/memory T cells contribute to the allogeneic MLR and mandate further investigation of the impact of siplizumab on alloreactive naïve T cells. Abstract : The anti‐CD2 monoclonal antibody (siplizumab) depletes alloreactive effector memory T cells, but spares and allows the expansion of donor‐specific regulatory T cells in vitro.